An Axiological Aspect of Terrorism: Remarks on Scott Atran's Perspective. Issue 2 (2nd April 2016) - Szocik, Konrad
ABSTRACT: "The philosophers have only interpreted the world, in various ways. The point, however, is to change it, " said Karl Marx. Any experts about terrorism interpret and describe it. The point is to stop terrorism. Current terrorism, especially suicide terrorism, involves some features, such as sacred values, family-like group, religious reference, social support, and manipulation. Here, I briefly review some of these basic features which are the core of Scott Atran's approach to the study of terrorism.